Brick Kilns in Kathmandu Valley: Current status, environmental impacts and future options - Raut, A. K. (Himalayan Journal of Sciences, 2006)
'Kathmandu Valley' is vulnerable to air pollution problem due to its topography, which restricts the wind movement and allows pollutants to remain within the valley. Brick kilns, operating in the Valley, are known to be a prime cause of air pollution. There are currently more than 125 brick kilns operating in Kathmandu valley deteriorating its air quality and degrading the health of the people living near the kilns. Recent studies have found that the concentration of particulate matter in the air in an area with brick kilns is three times higher when the kilns are operating than during the off-season. Similarly, the health of students studying at a school situated near a brick kiln was found to be significantly worse than that of students studying in a similar school but located in an area without brick kilns. Other environmental costs of the brick kilns are the reduction in the soil fertility, reduced visibility, drying ground water sources. The use of an old and inefficient technology called Bull's Trench kilns and low quality fuel are the main causes of the problem. Recently the government has decided to ban Bulls Trench brick kilns in Kathmandu in a year and a half. As a result, entrepreneurs are searching for environment friendly and cost effective alternative technologies. There are some technologies currently in practice in India like Vertical Shaft Brick Kiln, Fixed Chimney Kilns which are environment friendly and economically sound. Introduction to these technologies in Nepal can save both ecology and economy.Himalayan Journal of Sciences 1(1): 59-61, 2003